Pendampingan Penyusunan Program Latihan Melalui Model SMART Training Pada Pelatih Atletik Pengcab PASI Kabupaten Langkat - Sunarno, Agung; Suprayitno; Sihombing, Hardodi; Mhd. Yan Ahadi (Jurnal Pengabdian Keolahragaan dan Sains, 2025)
This community service activity was aimed to assist athletic coaches in Langkat in designing training programs using the SMART (Specific, Measurable, Achievable, Relevant, and Time-bound) model. The method used included training, mentoring, and evaluation stages. A total of 20 coaches participated in practical sessions to use sport science tools and understand athlete talent identification. The result showed significant improvement in understanding coaching techniques and application of SMART methods, as shown by the pre-post training assessment. The outcome enhanced the ability of coaches to develop structured programs based on measurable parameters. Kegiatan pengabdian ini bertujuan untuk mendampingi pelatih atletik di Langkat dalam menyusun program latihan berbasis model SMART (Specific, Measurable, Achievable, Relevant, dan Time-bound). Metode yang digunakan meliputi pelatihan, pendampingan, serta evaluasi. Sebanyak 20 pelatih mengikuti kegiatan praktik pemanfaatan alat sport science dan memahami identifikasi bakat atlet. Hasil menunjukkan peningkatan pemahaman dan keterampilan pelatih secara signifikan setelah pelatihan. Program ini meningkatkan kemampuan pelatih dalam merancang latihan yang terstruktur dan berbasis data.